The Shift of Siri’ Values among the Bugis in Pre-Wedding Photography: An Analysis of Islamic Family Law - Prasetio, Tri Bambang; Rusdaya Basri; Zainal Said; Agus Muchsin; Islamul Haq (Al-Iftah: Journal of Islamic studies and society, 2025)
This study examines the shifting meaning of Siri’ in the practice of pre-wedding photography among the Bugis community in Parepare City. In Bugis culture, Siri’ represents honor, modesty, and respect for tradition, values strictly preserved, especially by couples preparing for marriage. However, modernity and contemporary lifestyle have increased the popularity of pre-wedding photography. From an Islamic law perspective, interactions between unmarried men and women are restricted, including in pre-wedding photo sessions, creating tension between modern practices, cultural values, and religious norms.The research uses a field-based qualitative design with an empirical approach. Data were collected through observation, interviews, and documentation. Primary sources included religious leaders, photographers, and couples involved in pre-wedding photography, while secondary sources comprised literature on Siri’ and Islamic family law.The findings highlight three main points: (1) Pre-wedding photography is now part of contemporary wedding trends despite some perceptions of inappropriateness, driven by technology, social media, and visual representation. (2) There is a significant shift in Siri’s interpretation, moving from strict pre-marital modesty toward a symbolic understanding compatible with modern lifestyles. (3) Islamic law and Siri’ values respond critically and selectively; Islamic law rejects practices that violate sharia, while Siri’ has transformed yet persists in the community’s consciousness.These findings imply that Bugis cultural identity is adapting, with traditional values like Siri’ being reinterpreted rather than abandoned to accommodate modern social realities. This shift challenges communities to balance cultural expectations, religious norms, and contemporary lifestyles, highlighting the need for clearer cultural guidance and context-sensitive Islamic legal education.